Heterogeneity in money holdings across euro area countries: The role of housing - Ralph Setzer; Paul van den Noord; Guntram B. Wolff (Deutsche Bundesbank, 2010)
In this paper we examine why monetary aggregates of euro area Member States have developed differently since the inception of the euro. We derive a money demand equation that incorporates housing wealth and collateral as well as substitution effects on real money holdings. Empirically, we show that cross-country differences in real balances are determined not only by income differences, a standard determinant of money demand, but also by house price developments. Higher house prices and higher user costs of housing are both associated with larger money holdings. Country-specific money holdings are also connected with structural features of the housing market.
Keywords: E41; E51; E52; 330; Money; housing; national contribution; euro area; Geldnachfrage; Wohneigentum; Immobilienpreis; Schätzung; Eurozone